2018
DOI: 10.1182/blood-2018-99-111539
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Immune Gene Signatures Correlate with Response to Flotetuzumab, a CD123 × CD3 Bispecific Dart® Molecule, in Patients with Relapsed/Refractory Acute Myeloid Leukemia

Abstract: Background. The therapeutic approach in patients (pts) with acute myeloid leukemia (AML) has not changed substantially in >30 years. The introduction of new treatment strategies, including immunotherapy, remains a priority. Flotetuzumab, a CD123 × CD3 bispecific DART immunotherapy, is being tested in a phase 1/2 study of relapsed/refractory (R/R) AML. We previously showed that AML pts with an immune-enriched and IFN-γ-dominant tumor microenvironment (TME) experience significantly shorter relapse-free surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…The "inflamed/non-inflamed" AML dichotomy might explain why patients with identical AML entities and risk profiles may have different outcomes that deviate from the initial ELN prognostic prediction (42). Recent research has demonstrated that an "inflamed" AML immune profile can predict the resistance to cytotoxic therapy but also the patient's responsiveness to immunotherapies such as ICBs or DART (9,29,43). However, future research is necessary to investigate how B7 immune profiling can complement the predictive ability of the ELN risk classification and guide immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The "inflamed/non-inflamed" AML dichotomy might explain why patients with identical AML entities and risk profiles may have different outcomes that deviate from the initial ELN prognostic prediction (42). Recent research has demonstrated that an "inflamed" AML immune profile can predict the resistance to cytotoxic therapy but also the patient's responsiveness to immunotherapies such as ICBs or DART (9,29,43). However, future research is necessary to investigate how B7 immune profiling can complement the predictive ability of the ELN risk classification and guide immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Using large cohorts of subjects, the current study is the first to reveal underlying transcriptomic features that stratify the TME of AML into immune subtypes and may assist therapeutic predictions by defining patients who will potentially derive the greatest benefit from immunotherapies 11,46 . We identified two subtypes of differentially-infiltrated tumors, an observation that was validated in independent childhood and adult AML series, reinforcing the notion that unique molecular features can distinguish AML across age groups 33…”
Section: Discussionmentioning
confidence: 99%
“…T-cell markers and cytolytic effectors (CD8A, CD8B, GZMB, PRF1), counter-regulatory immune checkpoints and immunotherapy drug targets (IDO1, CTLA4, PD-L1 and BTLA), and molecules involved in antigen processing and presentation (TAP1, TAP2, HLA-A, HLA-B and HLA-C). Conceivably, high T-cell infiltration, MHC expression and PD-L1 levels in the immune-infiltrated AML subtype reflected a pre-existing IFN-γ-driven adaptive immune response which has previously been associated with suppressed anti-tumor immune reactivity 13,26 , but also with immunotherapy responses in patients with solid tumors 9,18,27 and AML 11 . The expression of STAT1, a central component of the IFN-γ signaling pathway and predictor of response to immune checkpoint blockade 28 , was more strongly correlated with the presence of T-cell inhibitory receptors TNFRSF14 (a ligand for the immunoglobulin superfamily members BTLA and CD160), PD-L1, HAVCR2 (Tim-3) and LAG-3, and with IFN-stimulated genes MX1, IFIT1 and IRF1 in the immune-infiltrated relative to the immunedepleted subtype, consistent with their coordinated regulation in an inflamed TME (Fig.…”
mentioning
confidence: 88%
See 2 more Smart Citations